How frequent is absolute femoral retroversion in symptomatic patients with cam- and pincer-type femoroacetabular impingement? - Malin K. Meier; Jelena Reche; Florian Schmaranzer; Hendrik von Tengg-Kobligk; Simon D. Steppacher; Moritz Tannast; Eduardo N. Novais; Till D. Lerch (Bone & Joint Open, 2022)
Aims: The frequency of severe femoral retroversion is unclear in patients with femoroacetabular impingement (FAI). This study aimed to investigate mean femoral version (FV), the frequency of absolute femoral retroversion, and the combination of decreased FV and acetabular retroversion (AR) in symptomatic patients with FAI subtypes. Methods: A retrospective institutional review board-approved observational study was performed with 333 symptomatic patients (384 hips) with hip pain due to FAI evaluated for hip preservation surgery. Overall, 142 patients (165 hips) had cam-type FAI, while 118 patients (137 hips) had mixed-type FAI. The allocation to each subgroup was based on reference values calculated on anteroposterior radiographs. CT/MRI-based measurement of FV (Murphy method) and AV were retrospectively compared among five FAI subgroups. Frequency of decreased FV < 10°, severely decreased FV < 5°, and absolute femoral retroversion (FV < 0°) was analyzed. Results: A significantly (p < 0.001) lower mean FV was found in patients with cam-type FAI (15° (SD 10°)), and in patients with mixed-type FAI (17° (SD 11°)) compared to severe over-coverage (20° (SD 12°). Frequency of decreased FV < 10° was significantly (p < 0.001) higher in patients with cam-type FAI (28%, 46 hips) and in patients with over-coverage (29%, 11 hips) compared to severe over-coverage (12%, 5 hips). Absolute femoral retroversion (FV < 0°) was found in 13% (5 hips) of patients with over-coverage, 6% (10 hips) of patients with cam-type FAI, and 5% (7 hips) of patients with mixed-type FAI. The frequency of decreased FV< 10° combined with acetabular retroversion (AV < 10°) was 6% (8 hips) in patients with mixed-type FAI and 5% (20 hips) in all FAI patients. Of patients with over-coverage, 11% (4 hips) had decreased FV < 10° combined with acetabular retroversion (AV < 10°). Conclusion: Patients with cam-type FAI had a considerable proportion (28%) of decreased FV < 10° and 6% had absolute femoral retroversion (FV < 0°), even more for patients with pincer-type FAI due to over-coverage (29% and 13%). This could be important for patients evaluated for open hip preservation surgery or hip arthroscopy, and each patient requires careful personalized evaluation. Cite this article: Bone Jt Open 2022;3(7):557–565.